ประสิทธิผลของโปรแกรมการฝึกสมาธิ ต่อพหุปัญญาของนักศึกษาชั้นปีที่ 1 วิทยาลัยเซนต์หลุยส์ - เลิศสาครศิริ มาลีวัล (Journal of The Royal Thai Army Nurses, 2016)
การวิจัยครั้งนี้เป็นการวิจัยกึ่งทดลอง ชนิด 1 กลุ่มทดสอบก่อนและหลังการทดลอง เพื่อศึกษาผลการฝึกสมาธิ เจริญสติในการส่งเสริมพหุปัญญาของนักศึกษาชั้นปีที่ 1 ประชากร คือ นักศึกษาชั้นปีที่ 1 วิทยาลัยเซนต์หลุยส์ หลักสูตรพยาบาลศาสตรบัณฑิตศิลปศาสตรบัณฑิต และกายภาพศาสตรบัณฑิต ประจำปีการศึกษา 2557 จำนวน 194 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลเป็นแบบสอบถามประกอบด้วยข้อมูลส่วนบุคคล พหุปัญญา ความคิด เห็นและความพึงพอใจต่อการฝึกสมาธิ เจริญสติที่ผ่านการตรวจความตรงเชิงเนื้อหาโดยผู้ทรงคุณวุฒิ 3 ท่าน หาค่าดัชนีความตรงได้เท่ากับ .80 และค่าความเที่ยงได้เท่ากับ .970และ .913 ตามลำดับ วิเคราะห์ข้อมูลโดยหาค่าความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์ความแตกต่างของค่าเฉลี่ยด้วยสถิติทดสอบทีผลการวิจัย พบว่า ภายหลังเข้าร่วมกิจกรรมการฝึกสมาธิ เจริญสติ นักศึกษาชั้นปีที่ 1 มีคะแนนเฉลี่ยพหุปัญญาโดยรวมและความคิดเห็นอยู่ในระดับมาก เท่ากับ 5.21 และ 4.33 สูงกว่าก่อนการเข้าร่วมกิจกรรมที่มีคะแนนเฉลี่ยเท่ากับ 4.94 และ 4.07 ตามลำดับอย่างมีนัยสำคัญทางสถิติที่ระดับ .001 ผลการศึกษาบ่งชี้ว่าโปรแกรมการฝึกสมาธิมีผลให้เกิดการพัฒนาพหุปัญญาของนักศึกษาโดยรวม ซึ่งจะเป็นผลให้นักศึกษามุ่งนำไปใช้ประโยชน์ในด้านการเรียน การปฏิบัติงานตามหน้าที่ความรับผิดชอบ สามารถตัดสินใจ และแก้ปัญหาได้อย่างเหมาะสมในการดำเนินชีวิต The Effectiveness of Meditation Program toward Multiple Intelligences among the First Year Students at Saint Louis College This research was a quasi-experiment with pretest-posttest one group design. The purpose of this research was to study the effect of meditation and mindfulness in promoting multiple intelligences of the first year students. The population included 194 first year students, who studied in the faculties of nursing, liberal art and physical therapy in the academic year 2014 at Saint Louis College. The research tool was a questionnaire including personal data, multiple intelligences, the opinion and satisfaction for meditation and mindfulness. The questionnaire was validated by a group of 3 experts. The content validity index (CVI) of the questionnaire was .80, the reliability were .970 and .913, respectively. The data were analyzed by frequency, percentage, mean, standard deviation, and t-test. The results indicated that the first year students had average scores of total multiple intelligences and the opinion in the high level after participating in the activity of meditation and mindfulness. The average scores were 5.21 และ 4.33 which were statistically higher than average scores before participating activities (μ = 4.94 and 4.07, respectively) at p<.001. The findings suggested that the meditation program could promote multiple intelligences of the first year students. Finally, this was very useful for students to use in learning, performing their responsibilities, making decisions and solving problems appropriately in their life.